Insects [electronic resource] : [preface]. - Stefansson, Vilhjalmur, 1879-1962.; Canadian Arctic Expedition (1913-1918) (Ottawa : F.A. Acland, 1922)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 3. Includes list of titles in the series. Errata (for all v. 3)--p. [6-7] "This volume is one of a series of reports dealing with the results of the Canadian Arctic Expedition, 1913-1918, which was led by Mr. Wilhjalmur Stefansson ."--p. [2] Electronic reproduction. Mode of access: Internet. 44